Electronic Paint: Understanding Children's Representation through their Interactions with Digital Paint. - Matthews, John; Seow, Peter (International Journal of Art & Design Education, 2007)
This article investigates very young children's use of a stylus-driven, electronic painting and drawing on the tablet PC. The authors compare their development in the use of this device with their use of other mark-making media, including those which derive from pencil and paper technologies and also with mouse-driven electronic paintbox programs. After experience of using of electronic paint, two of the children were introduced to simple programming software. The authors wanted to find out how the introduction of electronic, digital, interactive devices impact upon children's development in semiotic understanding.